2019
DOI: 10.1016/j.omto.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

STING Restricts oHSV Replication and Spread in Resistant MPNSTs but Is Dispensable for Basal IFN-Stimulated Gene Upregulation

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are an aggressive soft-tissue sarcoma amenable only to surgical resection. Oncolytic herpes simplex viruses (oHSVs) are a promising experimental therapy. We previously showed that basal interferon (IFN) and nuclear factor κB (NFκB) signaling upregulate IFN-stimulated gene (ISG) expression and restrict efficient viral infection and cell-to-cell spread in ∼50% of tested MPNSTs. Stimulator of Interferon Genes (STING) integrates DNA sensor activity and mediates dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Oncolytic virus spread, assessed by viral-encoded eGFP expression, evidenced the formation of large lysis plaques in Sting knockout cells, compared to the viral restraint observed in the Sting wild-type statuses of both parental cell lines ( Figure 2 A,B). Interestingly, as reported in the independent scientific literature [ 24 , 25 , 26 , 27 ], we confirmed that the efficiency of viral replication is actually related to Sting expression, since Sting knock down cells show an intermediate level of viral replication, compared to Sting wild-type and knockout cells ( Figure S4 ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Oncolytic virus spread, assessed by viral-encoded eGFP expression, evidenced the formation of large lysis plaques in Sting knockout cells, compared to the viral restraint observed in the Sting wild-type statuses of both parental cell lines ( Figure 2 A,B). Interestingly, as reported in the independent scientific literature [ 24 , 25 , 26 , 27 ], we confirmed that the efficiency of viral replication is actually related to Sting expression, since Sting knock down cells show an intermediate level of viral replication, compared to Sting wild-type and knockout cells ( Figure S4 ).…”
Section: Resultssupporting
confidence: 89%
“…These data demonstrate that Sting pathway efficiently counteracts the infection of HSV-1, even in the presence of functional viral anti- Sting genes (e.g., γ34.5) held by the non-attenuated R-LM113 and R-LM55 viruses [ 16 , 27 ]. Altogether, these data suggest that tumor cells with impaired DNA-sensing Sting pathway could potentially represent an improved target for oncolytic virotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations